Cafeto: café com afeto e a dialética do cuidado do si - FERREIRA, Lorena Priscila da Costa (2022)
This Course Completion Work aims to report the process of creation and execution of the performance called "Cafeto". In this process I narrate the importance of self care and how this internal care is established in relation to the other based on performance development. The term "Cafeto" is born from the union of two words: coffee and affection. Where I use coffee to activate memoirs of the participants and from the life reports, build a relationship of care from the self to the other, showing that every life story has significance not only for the sender, but also for the recipient . In addition, this research addresses my relationship with the people who helped in this creative process, since theater is one of the few arts that is not done alone. In this research is found theoretical basis for the performance of the performance with Renato Cohen. Regarding the care of the self, I dialogue with the ideas of Michel Foucault and George Gurdjieff. Other authors of poetry who helped me in this research such as Flavio Venturini, Renato Russo, Leandro Flores, Fátima Araujo, Manoel de Barros, Martha Zamora and with letters of passion of Frida Kahlo that helped me in the construction of poetic-academic writing. As well as, it is present in the development of the research methodology the life story of Waldir Abreu.